Desarrollo de cinco modelos matemáticos por medio de un algoritmo genético, para la predicción del corte de agua en cinco pozos del Campo Carrizales (2017)
This project was done to generate mathematical models able to predict the behavior of the percentage of production water, using a genetic algorithm. For each mathematical model, a history matching was made and the absolute error and the mean square error were calculated. Subsequently, the prediction of water cut was made for next two years under two scenarios of production. In the first scene, water cut was calculated when pump frequency remains constant and in the second scene, water cut was calculated when pump frequency is modified at a constan monthly rate over the next two years. Finally, financial evaluation was performed through the net present value methodology and the operating cost of each scene were calculated, resulting in second scenario being the most profitable scenario for the company.